The Secret of Antibiofilm Agent for Burn Injury : A Systematic Review - Gembong Satria Mahardhika; Prahapsari Rupadha; Maudy Surya Pradisa (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Burn injuries remain to be a significant issue. The environmental condition in Indonesia contributes to the prevalence of diverse bacterial infection associated with different types of wounds, including burns. The biofilms production at the site of burn wounds significantly contributes to the ineffectiveness of burn treatment protocols. Hereby in this paper we discuss about the mechanism of antibiofilm and the novel therapy for the burn injury.  This study was classified as a systematic review approach. The compilation of references will be derived from journal articles obtained using search engines such as PubMed, Google Scholar, and EBSCO. Subsequently, the authors proceed to gather and reevaluate pertinent material and scholarly articles. The occurrence of biofilm is closely associated with burn injuries. These bacterial communities evoke antibiotic resistance, hence impeding the effectiveness of conventional treatment approaches. It is noteworthy that substantially 60% of burn-related mortality is attributed to biofilms. This condition has the potential to develop into a persistent wound, ultimately resulting in sepsis. The development of biofilm or invasive burn wound infection serves as a significant catalyst for the occurrence of sepsis. The administration of anti-biofilm drugs holds significant potential in this context as a proactive measure for reducing the worsening effects of burns. Conclusion : The utilization of anti-biofilm agents has the potential to serve as an innovative therapeutic approach for the treatment of burn wounds in the future. Further investigation is required to explore the potential outcome as well as adverse effects of this drug linked to its potency.